2015
DOI: 10.5665/sleep.4394
|View full text |Cite
|
Sign up to set email alerts
|

Association between Sleep Duration and Mortality Is Mediated by Markers of Inflammation and Health in Older Adults: The Health, Aging and Body Composition Study

Abstract: Inflammatory markers, lifestyle, and health status explained mortality risk associated with short sleep, while the mortality risk associated with long sleep was explained predominantly by lifestyle and health status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
92
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(101 citation statements)
references
References 42 publications
7
92
1
1
Order By: Relevance
“…Our main novel findings is that the mortality risk associated with prolonged nighttime blood oxygen desaturation (≥10% TST SaO 2 <90%) and short sleep duration was substantively attenuated by adjustment for inflammatory burden alone and other medical burden/lifestyle factors; note that the attenuation after adjusting for inflammatory burden and other health status covariates separately (Models 2a and 2b) then together (Model 3) suggests these adjustments accounted for some shared and some distinct variance in mortality risk that was attributed to these sleep characteristics (in Model 1). These findings are consistent with prior research on self-reported sleep duration, inflammation, disease, and mortality (40), and suggests these aspects of sleep may be linked to mortality through concurrent inflammation and disease.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our main novel findings is that the mortality risk associated with prolonged nighttime blood oxygen desaturation (≥10% TST SaO 2 <90%) and short sleep duration was substantively attenuated by adjustment for inflammatory burden alone and other medical burden/lifestyle factors; note that the attenuation after adjusting for inflammatory burden and other health status covariates separately (Models 2a and 2b) then together (Model 3) suggests these adjustments accounted for some shared and some distinct variance in mortality risk that was attributed to these sleep characteristics (in Model 1). These findings are consistent with prior research on self-reported sleep duration, inflammation, disease, and mortality (40), and suggests these aspects of sleep may be linked to mortality through concurrent inflammation and disease.…”
Section: Discussionsupporting
confidence: 91%
“…To our knowledge, the only prior investigation of whether inflammation attenuates sleep-related mortality risk relied on self-reported sleep duration (40). The current report therefore aimed to determine whether objectively measured sleep characteristics are associated with mortality risk independent of concurrent inflammation.…”
mentioning
confidence: 99%
“…A total of 74 studies met the inclusion criteria; the process of study selection is shown in Figure 1 8, 9, 11, 12, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89,...…”
Section: Resultsmentioning
confidence: 99%
“…** References 11, 21, 23, 25, 26, 27, 29, 32, 33, 34, 36, 39, 40, 41, 44, 46, 47, 48, 49, 51, 52, 53, 54, 56, 57, 61, 64, 66, 68, 70, 71, 72, 77, 79, 80, 84, 86, 87, 88.…”
Section: Notesmentioning
confidence: 99%
“…and mortality. 9,10 Evidence also suggests that electroencephalography (EEG) based sleep time can be used to identify a "normal sleep duration" insomnia phenotype and positively predict those individuals most likely to respond to cognitive behavioral treatment intervention (the now recognized first-line therapy for insomnia). 11 Additional phenotypes are emerging through the use of sleep biomarkers related to depressive and anxiety disorders and/or stress-related insomnia.…”
Section: Scientific Investigationsmentioning
confidence: 99%